Ultrastructure of oogenesis of two oviparous demosponges: Axinella damicornis and Raspaciona aculeata (Porifera) - Riesgo, A.; Maldonado, M. (Tissue and Cell, 2009)
We investigated the cytology of the oogenic cycle in two oviparous demosponges, Axinella damicornis and Raspaciona aculeata, during 2 consecutive years both by light and electron microscopy. Oocytes of both species were similar in their basic morphological features but differenceswere noticed in time required to complete oocyte maturation and mechanisms of acquisition of nutritional reserves. The oogenic cycle of A. damicornis extended for 7–8 months in autumn-spring, while that of R. aculeata did it for 3–5 months in summer-autumn. Yolk of A. damicorniswas predominantly formed by autosynthesis. Oocytes endocytosed bacteria individually and stored them in groups in large vesicles. Bacteria were digested and lipidic material was added to the vesicles to produce a peculiar granular yolk hitherto unknown in sponges. Scarce cells carrying heterogeneous inclusions were observed in the perioocytic space, and were interpreted as putative nurse cells. Such cells were presumably releasing lipid granules to the perioocytic space. In contrast, large numbers of nurse cells were found surrounding the oocytes of R. aculeata. They transported both lipid granules and heterogeneous yolk bodies to the oocytes. R. aculeata also produced some of their yolk by autosynthesis. The involvement of nurse cells in the vitellogenesis of R. aculeata shortened the oocyte maturation, whereas a largely autosynthetic vitellogenesis in A. damicornis prolonged the duration of oogenesis.